Comments vs. One-Click Reactions: Seeking and Perceiving Social Support on Social Network Sites. Issue 5 (1st December 2020) - Li, Siyue; Coduto, Kathryn D.; Song, Chi
ABSTRACT: Balancing the needs of support seeking and self-presentation becomes an important question to investigate on social network sites (SNSs). This study examined 1) how support seekers can effectively elicit support on SNSs and 2) if they perceive a textual comment and a one-click reaction (e.g., Like, Love) differently on supportiveness. Our results showed that mixed-valenced support-seeking posts received more comments and one-click reactions than posts that only contain negative content. Posts that involved direct requests for support were more successful in eliciting comments than posts that indirectly sought support. Further, support seekers perceived textual comments as more supportive than one-click reactions.